Influence of Social Media on News Consumption and Credibility in Nigeria - Eric Msughter Aondover; Emmanuel Chukwuemeka Igwe; Omolara Oluwabusayo Akin-Odukoya; Muhammad Ridwan (Budapest International Research and Critics University, 2024)
This study analysed the influence of social media on news consumption and credibility, with reference to Lagos State. The study sought to assess the net benefits of social media as a source of information in Nigeria by determining the credibility of news obtained on various social media platforms in the country, and analyzing the challenges caused by social media through misinformation and fake news. Source Credibility Theory was employed in the study. A well-structured questionnaire served as instrument for data collection. The study made use of simple percentages and frequency statistics to analyse the data collected. Results from the analysis show that there is misinformation on social media platforms. Results show that Facebook is the greatest source of misinformation, followed by WhatsApp, and TikTok. Results show that social media misinformation is strongest by age, followed by education, income, and occupation. This implies that younger generations are most susceptible to social media misinformation, while those with lower education are also susceptible to misinformation from social media platforms. Therefore, not every user of social media can militate against social media misinformation. Based on these findings, this study recommends some measures of social media regulation. Verified accounts should be granted permission across social media platforms as source of information and news to users of social media. Also, the study recommends that social media users must ensure that they verify information and news received on social media before making use of such information.